Frequency of Depression in Patients with Diabetes Mellitus (Medical Forum Monthly, 2021)
Objective: In this study, we will determine the prevalence of depression in diabetes and its association with gender and duration of diabetes.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the OPD of diabetes in Civil Hospital Karachi from June 2019 to Jan 2020.Materials and Methods: 273 previously confirmed diabetic patient for 2 or more years of either gender between age group 21-65 were enrolled after informed consent. Diagnosis and sternness of depression was evaluated through Hamilton rating scale for depression (HAM-D).Results: Out of 273, 92 (33.6%) patients had depression according to HAM-D scale. Depression was more common in females in comparison to male; though, the disparity was not adequate (60.9% vs. 39.1%. p value: 0.07). Men had 22.2% mild depression, 50% moderate depression and 27.8% severe depression. Female had 18% mild depression, 48% moderate depression and 34% severe depression.Conclusion: Depression is very prevalent in diabetic population, particularly in female and participants with recent duration of diabetes. It is important that psychological evaluation of diabetic patient should be done periodically, and appropriate treatment should be common after diagnosis.